2022
DOI: 10.1016/j.pmedr.2022.101722
|View full text |Cite
|
Sign up to set email alerts
|

Youth athletes sleep more, practice less, and may lose interest in playing sports due to social distancing mandates

Abstract: In-person sport participation was suspended across the United States in the spring of 2020 to slow the spread of the novel coronavirus (COVID-19). The purpose of this study was to survey the impact of COVID-19 on young athletes during a period of social and organized sports restrictions. An anonymous cross-sectional survey study was conducted of youth athletes in the midst of social distancing mandates and consisted of six components: demographics, sport participation, changes in sport-related goals/aspiration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…Youth athletes in the United States reportedly trained for 9.7 h per week on average before the pandemic. This number reduced significantly to 6.4 h per week during the pandemic [10]. Although we could not directly compare the training time because such information was unavailable in our study, we posit that the lack of team practice may have detrimentally influenced the youth baseball players.…”
Section: Baseball Activitymentioning
confidence: 87%
See 2 more Smart Citations
“…Youth athletes in the United States reportedly trained for 9.7 h per week on average before the pandemic. This number reduced significantly to 6.4 h per week during the pandemic [10]. Although we could not directly compare the training time because such information was unavailable in our study, we posit that the lack of team practice may have detrimentally influenced the youth baseball players.…”
Section: Baseball Activitymentioning
confidence: 87%
“…In addition, the sleeping time during the state of emergency was significantly longer than that before the pandemic, although the change in sleeping time was only 8 min. Youth athletes in the United States reported significantly increased average sleeping time per night, from 7.9 h before the pandemic to 9.4 h during the pandemic [10]. Notably, the National Sleep Foundation in America has recommended 9-11 h of sleep daily for school-aged children [18].…”
Section: Lifestylementioning
confidence: 99%
See 1 more Smart Citation
“…The results of the assessed articles showed conflicting or inconclusive findings. It was observed that 69% of these studies (Chandler et al, 2021;Elce et al, 2022;Filice, 2022;Kurniarobbi et al, 2022;Mon-López et al, 2020;Romdhani, Fullagar, et al, 2022;Romdhani, Rae, et al, 2022;Vinu, 2021;Vitale et al, 2021) showed reduced sleep health among athletes whereas 23% of these studies (Beranek et al, 2022;Ellis et al, 2022;Facer-Childs et al, 2021) expressed the inverse. Only 7% studies (da Silva Santos et al, 2021) portrayed no effect.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a possibility that factors including limitation in exercise and physical activities, increased screen time, increase in anxiety, stress and depression due to the spread of negative news such as deaths and losses during pandemic through social media and other sources might have played a vital part in effecting athletes' sleep health (Armaou et al, 2020;Ellis et al, 2022;Facer-Childs et al, 2021). Subsequently, it was also observed that those athletes who effectively upheld their pre-Covid routines appeared to have retained sleep health (Keemss, Sieland, Pfab, & Banzer, 2022).…”
Section: Discussionmentioning
confidence: 99%